Determination of simazine and terbuthylazine in olive oil by high performance liquid chromatography with ultraviolet detector - Sobhanzadeh, E.; Bakar, N.K.A.; Abas, M.R.B.; Nemati, K. (2010)
An effective matrix solid-phase dispersion extraction for the determination of simazine and terbuthylazine in olive oil is described. The proposed methodology is based on partitioning liquid-liquid extraction and low temperature precipitation followed by matrix solid-phase dispersion (MSPD), using aminopropyl as dispersant material with a clean-up performed in the elution step with florisil and graphitized carbon (60:40, w/w). Related important factors influencing the extraction efficiency, such as, type of eluent and its volume, type of adsorbent for clean-up step, amount of dispersant material and the ratio of mobile phase were studied and optimized. The method was validated in terms of accuracy and precision (intra-day and inter-day), using spiked samples at different concentration levels. The recoveries were satisfactory (> 91) and limits of detection and quantification as Î¼g of herbicides/g of olive oil sample were: 0.0127 and 0.0540 Î¼g g-1 for simazine, 0.027 and 0.14 Î¼g g-1 for terbuthylazine, respectively.